ANALISIS PELAKU PERNIKAHAN DINI DI DESA PRINGGONDANI KECAMATAN SUMBER JAMBE KABUPATEN JEMBER - Lujeng Rizkiyah; Faridy Faridy (JURNAL HAKAM, 2020)
The phenomenon of marriage at a young age is still happening in the community, especially in Pringgondani Village, Sumber Jambe District, Jember Regency. Marriage at an early age is the practice of marriage between a man and woman as husband and wife with the aim of forming a happy and eternal household, but the ages of both of them have not yet reached the predetermined date.Early marriage in Pringgondani Village, Sumber Jambe District is caused by several factors including tradition / culture factors, parental factors, educational factors, and customs factors. Early marriage also has several positive impacts, namely faster independence, preventing adultery and reducing the economic burden on parents, while the negative impact is the loss of adolescence and play for adolescents and immature reproductive organs, especially if pregnancy occurs. And the 'urf' analysis of early marriage in Pringgondani Village is if viewed from the object, it includes 'urf' amali, seen from its scope including 'urf khos' and if seen from its validity it includes 'ufr shahih because it does not contradict syara's argument'.